Sticky apps, not sticky hands: A systematic review and content synthesis of hand hygiene mobile apps. (28th June 2021) - Gasteiger, Norina; Dowding, Dawn; Ali, Syed Mustafa; Scott, Ashley Jordan Stephen; Wilson, Paul; van der Veer, Sabine N
Abstract: Objective: The study sought to identify smartphone apps that support hand hygiene practice and to assess their content, technical and functional features, and quality. A secondary objective was to make design and research recommendations for future apps. Materials and Methods: We searched the UK Google Play and Apple App stores for hand hygiene smartphone apps aimed at adults. Information regarding content, technical and functional features was extracted and summarized. Two raters evaluated each app, using the IMS Institute for Healthcare Informatics functionality score and the Mobile App Rating Scale (MARS). Results: A total of 668 apps were identified, with 90 meeting the inclusion criteria. Most (96%) were free to download. The majority (78%) intended to educate or inform or remind users to hand wash (69%), using behavior change techniques such as personalization and prompting practice. Only 20% and 4% named a best practice guideline or had expert involvement in development, respectively. Innovative means of engagement were used in 42% (eg, virtual or augmented reality or geolocation-based reminders). Apps included an average of 2.4 out of 10 of the IMS functionality criteria (range, 0-8). The mean MARS score was 3.2 ± 0.5 out of 5, and 68% had a minimum acceptability score of 3. Two had been tested or trialed. Conclusions: Although many hand hygiene apps exist, few provide content on best practice. Many did not meet the minimum acceptability criterion for quality or were formally trialed or tested. Research should assess the feasibility and effectiveness of hand hygiene apps (especially within healthcare settings), including when and how they "work." We recommend that future apps to support hand hygiene practice are developed with infection prevention and control experts and align with best practice. Robust research is needed to determine which innovative methods of engagement create "sticky" apps.